Engineered CRISPR-Cas9 nucleases with altered PAM specificities - Kleinstiver, Benjamin P. (Nature, 2015)
Although CRISPR-Cas9 nucleases are widely used for genome editing(1, 2), the range of sequences that Cas9 can recognize is constrained by the need for a specific protospacer adjacent motif (PAM)(3–6). As a result, it can often be difficult to target double-stranded breaks (DSBs) with the precision that is necessary for various genome editing applications. The ability to engineer Cas9 derivatives with purposefully altered PAM specificities would address this limitation. Here we show that the commonly used Streptococcus pyogenes Cas9 (SpCas9) can be modified to recognize alternative PAM sequences using structural information, bacterial selection-based directed evolution, and combinatorial design. These altered PAM specificity variants enable robust editing of endogenous gene sites in zebrafish and human cells not currently targetable by wild-type SpCas9, and their genome-wide specificities are comparable to wild-type SpCas9 as judged by GUIDE-Seq analysis(7). In addition, we identified and characterized another SpCas9 variant that exhibits improved specificity in human cells, possessing better discrimination against off-target sites with non-canonical NAG and NGA PAMs and/or mismatched spacers. We also found that two smaller-size Cas9 orthologues, Streptococcus thermophilus Cas9 (St1Cas9) and Staphylococcus aureus Cas9 (SaCas9), function efficiently in the bacterial selection systems and in human cells, suggesting that our engineering strategies could be extended to Cas9s from other species. Our findings provide broadly useful SpCas9 variants and, more importantly, establish the feasibility of engineering a wide range of Cas9s with altered and improved PAM specificities.